The way of life of Sino-Indian families / Ragini Nadarajan - Ragini , Nadarajan (1994)
The study concentrated on interethnic marriage of the Chinese and Indian ethnic groups. The focus of study is the way of life of five Sino-Indian families from Georgetown, Penang. Chapter I presented t he proposal of this research, the objective, scope, methodology, concepts and theories as well as problems encountered in research. Chapter II discussed the characteristics of the Sino-Indian family. Basic characteristics were illustrated like the ethnic affiliation of each partner, the family composition and the type of marital union. Chapter III dealt with the relationship (in-laws and relatives) and the social interaction of the Sino-Indian family with the society around them. Chapter IV displayed the way of life of each Sino-Indian family involved in this reseach in the areas of performance of rites and rituals, participation in religious activities, medium of communication (language), preference and preparation of food. The final chapter presented the findings of this research, the significance of this researc to the individual and society and potential areas for future studies.